2004
DOI: 10.1038/nature02852
|View full text |Cite
|
Sign up to set email alerts
|

Early brain growth in Homo erectus and implications for cognitive ability

Abstract: Humans differ from other primates in their significantly lengthened growth period. The persistence of a fetal pattern of brain growth after birth is another important feature of human development. Here we present the results of an analysis of the 1.8-million-year-old Mojokerto child (Perning 1, Java), the only well preserved skull of a Homo erectus infant, by computed tomography. Comparison with a large series of extant humans and chimpanzees indicates that this individual was about 1 yr (0-1.5 yr) old at deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
120
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(132 citation statements)
references
References 20 publications
6
120
0
6
Order By: Relevance
“…Neonatal brain size was approximately 30 to 50% (the mean ratio is 34 to 36%) of early Pleistocene H. erectus adult brain size [~600 to 1067 ml (mean = 880 ml, n = 18 crania)] (21), an intermediate value between that of chimpanzees (~40%) and modern humans (~28%) (20). This new estimate of H. erectus neonatal brain size, in tandem with the revised age at death (~0.5 to 1.5 years) of the child's cranium from Perning (Mojokerto), Indonesia (<1.81 Ma) (22), suggests that H. erectus had a prenatal brain growth rate similar to that of humans but a postnatal brain and somatic growth rate intermediate between that of chimpanzees and humans (23).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Neonatal brain size was approximately 30 to 50% (the mean ratio is 34 to 36%) of early Pleistocene H. erectus adult brain size [~600 to 1067 ml (mean = 880 ml, n = 18 crania)] (21), an intermediate value between that of chimpanzees (~40%) and modern humans (~28%) (20). This new estimate of H. erectus neonatal brain size, in tandem with the revised age at death (~0.5 to 1.5 years) of the child's cranium from Perning (Mojokerto), Indonesia (<1.81 Ma) (22), suggests that H. erectus had a prenatal brain growth rate similar to that of humans but a postnatal brain and somatic growth rate intermediate between that of chimpanzees and humans (23).…”
mentioning
confidence: 99%
“…Crystal structures, biochemical assays, and single-molecule analyses have suggested different modes of interaction between RT and nucleic acid substrates, providing snapshots of the nucleoprotein complexes that illuminate the functional mechanism of RT [e.g., (17)(18)(19)(20)(21)(22)(23)(24)(25)]. Nevertheless, how the enzyme-substrate complex acquires specific functional configurations and switches between different functional modes remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…brain evolution | plasticity | hominins | neocortex | altriciality C ompared with nonhuman primates, human brains are significantly enlarged, reorganized, and have a disproportionately expanded neocortex (1)(2)(3). The fossil evidence demonstrates that these changes occurred in the hominin lineage over the last ∼6-8 My (4-9) in parallel with modifications to neurodevelopmental rates (10)(11)(12)(13). Although some of these changes have been linked to certain genetic variants in the human lineage [either shared with other late hominin species or exclusive to modern humans (14,15)], exploring brain evolution in hominins is challenging because of the limitations of the endocranial fossil record (4,5).…”
mentioning
confidence: 99%
“…Although life history models have suggested that this could be as old as the rise in meat consumption, the paleontological evidence tells a different story. Early Homo and Lower Pleistocene H. erectus display a more rapid development than extant humans (17)(18)(19). Perhaps the large-brained species of Middle Pleistocene hominins, which the Salé and SH14 specimens belong to, had already acquired most of the human pattern.…”
mentioning
confidence: 99%